THE ROLE OF MOTIVATION IN HUMAN LIFE - Kholiyorova Ch.D (Peerian Journals Publishing, 2022)
The formation of moral qualities of preschool children is carried out in different ways. It is expedient to form moral qualities using folk pedagogy. As a result, the formation of moral qualities becomes much easier.
Keywords: Motivation; work; teammate; goal